Chemical Tuning on Resonance Coupling in Gold Nanorod−Monolayer WS2 Heterostructures - Wen, Shiya; Deng, Shiyu; Chen, Kun; Chen, Huanjun; Deng, Shaozhi (Frontiers in Materials, 2021)
Resonance coupling between plasmonic resonances in metallic nanostructures and excitons in two-dimensional (2D) semiconductors has attracted much recent attention. The 2D semiconductor excitons are sensitive to external stimulus, enabling active tuning on the resonance couplings by physical, such as applying electrostatic gating, thermal scanning, etc., or chemical approaches. Among the others, chemical tuning approach has the advantage of facile implementation, high efficiency, and being capable of large-area tuning. Here, we report on chemical tuning of resonance coupling in heterostructures consisted of individual gold nanorods integrated with monolayer WS2. We showed that by incubating the heterostructures into a bis (trifluoro-methane) sulfonimide (TFSI) solution, the exciton transition strength of the WS2 will be enhanced significantly. As a result, the resonance coupling in the heterostructures evolved from a weak coupling regime to a strong coupling one, with the mode splitting energy increases from 94.96 meV to 105.32 meV. These findings highlight the potential of chemical treatment as an efficient technique for tailoring the interactions between plasmonic nanostructures and 2D semiconductors.